Evaluation and Creation of Web-based Resource Guides using SubjectsPlus - Manu, T. R.; Hasan, Nabi (Journal of Information and Knowledge, 2023)
The Resource Guide is a unified platform curated and administered by subject specialists, librarians, and liaisons, offering users access to a wide array of resources. Traditionally known by various names such as Pathfinder, bibliography, virtual reference collection, online guide, online tutorial, toolkit, or web guide, it serves as a comprehensive tool. Its primary purpose is to assist users in locating resources specific to their subject areas, staying updated on new resources, and connecting them to relevant, easily understandable information. At Central Library, IIT Delhi, diverse platforms like the library website, social media, online catalogues, Pathfinder, single search engine, and mobile app are utilized to promote library resources. However, these platforms may lack subject-level resources. This raises the question of designing and developing an online platform or resource base that consolidates and enables users to access various resources, including print resources, e-resources, professional development resources, open-access resources, and social media resources. This endeavour aims to meet the present and future needs of users in their respective disciplines. To explore this concept further, a pilot implementation of a web-based resource guide has been initiated at Central Library, IIT Delhi. This paper investigates how SubjectsPlus, an open-source tool, can facilitate the creation and management of web-based resource guides that promote the use of library and scholarly resources on the web.